Paget's disease of jaw bones as primary manifestation: A case report of a proper diagnosis made by general dentist. (7th May 2018) - Campolongo, Martin G.; Cabras, Marco; Bava, Luca; Arduino, Paolo G.; Carbone, Mario
Abstract : Objective: To present a case of early diagnosis mandibular Paget's disease of bone (PDB), recognised by a general dentist. Background: PDB is responsible of rapid bone resorption and disorganised bone formation. Materials and methods: The patient was a 72‐year‐old female patient complaining of dental malposition and blatant prognathism. Conclusion: Clinicians should consider PDB in differential diagnosis for an elderly patient undergoing unexplained alteration in face profile and occlusion.